"AMA NG TAHANAN": MASCULINITIES AND TRANSNATIONALISM IN LATER LIFE. (16th November 2018) - Kalaw, K
Abstract: The feminization of migration among countries has been an incessant trend over time. Lest we forget that men were the forerunners who initiated migrant labor and set the tone of global dependencies among nations. These transnational men in migration studies are often understudied and represented as solely economic actors devoid of subjectivities in contrast to their female transnational actors. This study sought to address the sparse literature on men's accounts on their inner worlds as juxtaposed to different spaces, e.g. personal and public. Specifically, this study explored and accounted the return experience of six (6) returnees after overseas work as refracted by age. The experience of old age of overseas male Filipino workers highlights the intersectionality of the event of old age and labor migration. The question explored was, "What is old age?" for these overseas Filipino returnees. This qualitative study is innovative as it connects several concerns in the gradual and increasing dialogues about the demand for migrant workers as juxtaposed to the graying population globally. Their return stories with the event of old age and their reentry to their families and community offer an opportunity to shed understanding on this urgent and relevant social phenomenon. The research utilizes the life course approach making it more meaningful to capture the inclusion of migration into the life trajectory of overseas male workers in later life while Filipino indigenous methodologies is used to contribute and be relevant for Philippine society.